PROFITS IN A THEORY. - Harold, Gilbert (The Accounting Review, 1939)
Abstract In this article, the author discusses theories and suggestions related to maximising profits of investments in stocks and securities. He reports that William Hughes, an actuary in London, has suggested that, it would be interesting if someone possessed of the necessary patience would ascertain "on paper" what would have been the results of a fund invested in common stocks as against one invested in high-grade bonds, but over a long period of years. Further on this suggestion, professor Irving Fisher, of Yale University, and some of his associates proposed that in order to keep pace with the cost of living one's investments would have to be in equities rather than in bonds, or in investments having equity connections. According to the common-stock theory, it is stated that assuming the continuing growth of industry, then over long periods of time investment in a diversified list of representative, leading, industrial common stocks will prove to be a better investment than will investment in high-grade bonds. Several consequences and limitations of this theory have been identified in terms of profit.